11,12,20-Trihydroxy-eicosa-8(Z)-enoic acid: a selective inhibitor of 11,12-EET-induced relaxations of bovine coronary and rat mesenteric arteries - Bukhari, Ishfaq A. (American Physiological Society, 2012)
Arachidonic acid is metabolized to four regioisomeric epoxyeicosatrienoic acids (EETs) by cytochrome P-450. 5,6-, 8,9-, 11,12-, and 14,15-EET are equipotent in relaxing bovine coronary arteries (BCAs). Vasorelaxant effects of EETs are nonselectively antagonized by 14,15-epoxyeicosa-5(Z)-enoic acid. The 11,12-EET analogs, 20-hydroxy-11,12-epoxyeicosa-8(Z)-enoic acid (20-H-11,12-EE8ZE) and 11,12,20-trihydroxyeicosa-8(Z)-enoic acid (11,12,20-THE8ZE) were synthesized and tested for antagonist activity against EET-induced relaxations in BCAs. In U-46619-preconstricted arterial rings, 5,6-, 8,9-, 11,12-, and 14,15-EET caused concentration-dependent relaxations with maximal relaxations ranging from 80 to 96%. Preincubation of arteries with 20-H-11,12-EE8ZE (10(−5) M) inhibited relaxations to 14,15- and 11,12-EET, but not 5,6- and 8,9-EET; however, greatest inhibitory effect was against 11,12-EET (maximal relaxation = 80.6 ± 4.6 vs. 26.7 ± 7.4% without and with 20-H-11,12-EE8ZE, respectively). Preincubation with the soluble epoxide hydrolase inhibitor (tAUCB, 10(−6) M) significantly enhanced the antagonist effect of 20-H-11,12-EE8ZE against 14,15-EET-induced relaxations (maximal relaxation = 86.6 ± 4.4 vs. 27.8 ± 3.3%, without and with 20-H-11,12-EE8ZE and tAUCB) without any change in its effect against 11,12-EET-induced relaxations. In contrast to the parent compound, the metabolite, 11,12,20-THE8ZE (10(−5) M), significantly inhibited relaxations to 11,12-EET and was without effect on other EET regioisomers. Mass spectrometric analysis revealed conversion of 20-H-11,12-EE8ZE to 11,12,20-THE8ZE by incubation with BCA. The conversion was blocked by tAUCB. 14,15-Dihydroxy-eicosa-5Z-enoic acid (a 14,15-EET antagonist), but not 11,12,20-THE8ZE (an 11,12-EET antagonist), inhibited BCA relaxations to arachidonic acid and flow-induced dilation in rat mesenteric arteries. These results indicate that 11,12,20-THE8ZE is a selective antagonist of 11,12-EET relaxations and a useful pharmacological tool to elucidate the function of 11,12-EET in the cardiovascular system.